Study of ‘Germanium and Nanoparticles' Optical Absorption Properties - Dr. Pawan Kumar (International Journal of Engineering and Management Research, 2020)
The optical absorption characteristics of noncrystalline and crystalline Ge nanoparticles with diameters ranging from ∼ 2.5 to 15 Å have been investigated using timedependent density functional theory at the B3LYP/6-31G level. On certain chosen Ge nanoparticles, hydrogen passivation and phosphorus doping were also computed. The optical absorption spectra of non-crystalline Ge nanoparticles evolve from numerous peaks to a continuous wide band as cluster size increases, while also exhibiting a consistent redshift. For both non-crystalline and crystalline Ge nanoparticles, doping phosphorus causes the absorption spectra to move toward the lower energy region. In contrast to crystalline Ge nanoparticles, non-crystalline Ge nanoparticles exhibit higher absorption in the visible range, independent of phosphorus doping.